1995
DOI: 10.1210/jcem.80.2.7852532
|View full text |Cite
|
Sign up to set email alerts
|

Insulin regulates testosterone and sex hormone-binding globulin concentrations in adult normal weight and obese men.

Abstract: There are no studies in vivo on the effects of insulin on androgens and sex hormone-binding globulin (SHBG) in men. We, therefore, investigated the effects of insulin suppression on testosterone and SHBG in two groups of eight nondiabetic adult obese men and six healthy normal weight men who underwent diazoxide treatment (100 mg, three times daily) for 7 days. Blood samples for hormone determination were obtained before the subjects had been selected for the study, immediately before diazoxide administration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 13 publications
6
60
0
6
Order By: Relevance
“…14,24 The 60-min time point was chosen as a previous study in adults has indicated postglucose load nadir testosterone values at this time. 11 In a separate visit conducted within 4 weeks of the visit described above, body composition was analysed via BOD POD (Life Measurement Incorporated, Concord, CA, USA) air-displacement plethysmography (ADP). 25 A standard, calibrated scale and wall-mounted stadiometer were used to measure weight and height, and body mass index (BMI) was calculated as weight (kg)/height (m) 2 .…”
Section: Protocolmentioning
confidence: 99%
“…14,24 The 60-min time point was chosen as a previous study in adults has indicated postglucose load nadir testosterone values at this time. 11 In a separate visit conducted within 4 weeks of the visit described above, body composition was analysed via BOD POD (Life Measurement Incorporated, Concord, CA, USA) air-displacement plethysmography (ADP). 25 A standard, calibrated scale and wall-mounted stadiometer were used to measure weight and height, and body mass index (BMI) was calculated as weight (kg)/height (m) 2 .…”
Section: Protocolmentioning
confidence: 99%
“…Furthermore, Pasquali et al . 38 demonstrated that inhibition of insulin secretion by giving diazoxide to normal weight and obese men led to increased SHBG levels. Acute hyperinsulinaemia has also been found to result in a small but significant reduction in SHBG concentration in healthy men.…”
Section: Contribution Of Shbgmentioning
confidence: 99%
“…Although the exact mechanism remains unknown, an inhibitory effect of insulin on the synthesis of SHBG seems a valid explanation, as direct inhibition of SHBG synthesis by insulin has been observed in HepG2 cells in the liver, both in vitro and in vivo (1, 6, 9, 14, 15, 16). Since there is (almost) no endogenous insulin production in T1DM patients, an increase of portal insulin concentration with CIPII and the subsequent increased hepatic insulinization may cause a more pronounced suppression of SHBG production.…”
Section: Discussionmentioning
confidence: 99%
“…Since there is (almost) no endogenous insulin production in T1DM patients, an increase of portal insulin concentration with CIPII and the subsequent increased hepatic insulinization may cause a more pronounced suppression of SHBG production. Apart from portal insulin concentrations, other factors such as glycemic control, insulin dose, insulin resistance, and the presence of microvascular complications have been suggested to influence SHBG concentrations (1, 4, 14, 17) among T1DM patiets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation